The Language of detection: A study of forensic and linguistic analysis in "Holmes" and "Dupin" stories - Hani, Hadiya Ahmed; Neneng Sri Lestari (Journal of Applied Linguistics, 2024)
This study explored the applications of forensic linguistics concerning two of Arthur Conan Doyle’s Sherlock Holmes stories, and the detailed linguistic analysis of Edgar Allan Poe’s ‘The Murders in the Rue Morgue.’ The key to the analysis of the two Sherlock Holmes stories involved the examination of how language was used to construct narratives of crimes and detection, the areas of discourse, narrative structure, and character development. The linguistic analysis of  Poe’s text involves discourse analysis, and pragmatic, and forensic linguistics revealing how language builds up mystery, tension, and resolutions as well as how character’s speech signals their aspirations and interactions. Additionally, it was shown not only how to engage the formalist principles in the interpretation of those texts directly connected with this movement but also, how linguistic methodology can be useful in the analysis of other works and in general, in the literary investigation. The study also highlighted the canonical significance and diversity of cases in the selected stories, demonstrating the varied methods through which language shapes the detective genre. By integrating secondary literature and employing rigorous analytical methods, the research contributes to a deeper understanding of forensic linguistics and its applications in both literary and legal contexts. The findings underscored the importance of linguistic analysis in enhancing the narrative structure and aiding in the detection of crime within detective fiction. Keywords : Forensic_Linguistics Analysis;  Holmes and Dupin_Stories